2018
DOI: 10.1186/s12875-018-0788-4
|View full text |Cite
|
Sign up to set email alerts
|

Not a magic pill: a qualitative exploration of provider perspectives on antibiotic prescribing in the outpatient setting

Abstract: BackgroundInappropriate prescribing of antibiotics poses an urgent public health threat. Limited research has examined factors associated with antibiotic prescribing practices in outpatient settings. The goals of this study were to explore elements influencing provider decisions to prescribe antibiotics, identify provider recommendations for interventions to reduce inappropriate antibiotic use, and inform the clinical management of patients in the outpatient environment for infections that do not require antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…These findings are consistent with previous research on perceptions of drivers of outpatient antibiotic prescribing. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In particular, the perception of patient demand as a driving force behind inappropriate prescribing practices continues to be a consistent finding across studies both in the USA and other countries. Similar perceptions have also been documented among inpatient physicians who believe that prescribers outside of hospitals are primarily responsible for antibiotic overuse and antibiotic resistance, underscoring the value for individual feedback on prescribing patterns to help these physicians recognise the need for antibiotic stewardship in their practice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are consistent with previous research on perceptions of drivers of outpatient antibiotic prescribing. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In particular, the perception of patient demand as a driving force behind inappropriate prescribing practices continues to be a consistent finding across studies both in the USA and other countries. Similar perceptions have also been documented among inpatient physicians who believe that prescribers outside of hospitals are primarily responsible for antibiotic overuse and antibiotic resistance, underscoring the value for individual feedback on prescribing patterns to help these physicians recognise the need for antibiotic stewardship in their practice.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies, including those from the USA and Europe, have shown that physicians consider patient demand and prescribing of other physicians to be primary drivers of inappropriate antibiotic prescribing. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In order to counteract these drivers of inappropriate prescribing, physicians have highlighted a need for improved public education around antibiotic resistance and the need for appropriate prescribing. 20-23 26 Additionally, studies from USA and European countries have shown that physician time constraints, fear of undertreating patients due to diagnostic uncertainty, and certain clinical factors are also seen as drivers of inappropriate prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…Findings confirmed those from other qualitative studies of antibiotic prescribing practices. 20,21 Clinicians identified typical barriers of insufficient time to learn and teach, diagnostic uncertainty, and patient demand for antibiotics, but they also identified preferences on how clinician-directed behavioral interventions should be implemented. They viewed making inappropriate decisions as having "caved" and perceived this was an issue for most clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for inappropriate antibiotic prescribing are multitude and originate at the interplay between doctor, patient and cultural context. Qualitative research identified many factors driving inappropriate prescribing, like diagnostic uncertainty, lack of guidelines, patient pressure and wrong expectations, time constraints, GPs’ habits, and an unstable GP-patient relationship due to lack of continuity of care [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%